2004
DOI: 10.1002/pssb.200405073
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved cathodoluminescence study on AlGaN layer fabricated by air‐bridged lateral epitaxial growth

Abstract: Structural properties of AlGaN layer on the GaN seed layer fabricated by air-bridged lateral epitaxial growth (ABLEG) have been studied by spatially resolved cathodoluminescence (CL) microscopy. The cross-sectional spatially resolved CL images of the ABLEG-AlGaN layer reveal that there are roughly three regions which have different main CL peaks. This result suggests that there are roughly three regions with the different Al contents. Before coalescence of the overgrown AlGaN wings, there are two regions of Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The heights of the voids in the HVAB structure markedly exceeds that of those in the conventional air-bridged LEO. [7][8][9] Figure 2 presents cross-sectional and plane-view CL images of conventional pendeo and HVAB structures. The crosssectional CL images in Figs.…”
Section: Air-bridged and Dot Air-bridged Epitaxial Lateral Overgrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…The heights of the voids in the HVAB structure markedly exceeds that of those in the conventional air-bridged LEO. [7][8][9] Figure 2 presents cross-sectional and plane-view CL images of conventional pendeo and HVAB structures. The crosssectional CL images in Figs.…”
Section: Air-bridged and Dot Air-bridged Epitaxial Lateral Overgrowthmentioning
confidence: 99%
“…[6] Kidoguchi et al proposed a new method of lateral growth, called air-bridged LEO, which improves on the wing tilting caused by conventional selective epitaxy. [7][8][9] Dry etching and standard photolithography were adopted herein to form trenches in a GaN template, and the sidewall of the GaN trenches was covered with a dielectric mask, such as SiN x or SiO 2 ,in an air-bridged LEO structure. After GaN had regrown, the voids in the air-bridged structure were buried in the coalesced GaN wings.…”
Section: Air-bridged and Dot Air-bridged Epitaxial Lateral Overgrowthmentioning
confidence: 99%
“…We have reported a CL study of ABLEG-AlGaN films, in which we showed that there are mainly three parts of aluminum inhomogeneity in ABLEG-AlGaN wing films. 18) We suggested that the aluminum inhomogeneity is due to three factors: (1) the different growth rates between the lateral and vertical directions, (2) the aluminum adatom diffusion on the (0001) and ( 1120) facets, and (3) the different effective growth temperatures of the ( 0001) and (11 20) facets. In this work, we examined further the spatial inhomogeneity of aluminum content in the main three parts of ABLEG-AlGaN films with various mask widths.…”
Section: Introductionmentioning
confidence: 99%